The Early Engagement Model in Product Development: Linking "Proof of Concept" to "Proof of Medical Value". (September 2016) - Iqbal, Sheikh Usman; Salimi, Tehseen; Dunlop, John; Paramore, L. Clark
In a rapidly changing health care environment, it is more important than ever that pharmaceutical manufacturers improve the quality and efficiency of their research and development efforts in order to help ensure the right drug gets to the right patient at the right time. The evolving role of the Medical Affairs, Health Economics & Outcomes Research (HEOR) and other functions engaged in evidence generation within the pharmaceutical industry is leading to earlier involvement in the clinical development process so that the proof of concept for new therapies can be more strongly linked to the proof of medical value. In this article, the authors outline key components of an Early Engagement Model that connects the proof of concept to proof of medical value through a systematic approach linking molecular profile with early insights on disease, unmet needs, stakeholder requirements, and patient-centric differentiation.